A novel key pre-distribution approach for high security and efficiency using LU-decomposition of matrix. (2016) - Choi, S.J.; Kim, K.T.; Youn, H.Y.
Wide-spread deployment of wireless sensor network (WSN) is emerging, which allows an economical solution for numerous applications. For the security of communication network, asymmetric cryptography is usually employed. This approach is, however, often unsuitable to WSN due to limited computational and energy power. Among various approaches the random key pre-distribution approach is regarded as the most effective one for WSN. Here one shortcoming is that a common key is not guaranteed to be found between any two communicating nodes. This paper proposes a new key pre-distribution scheme solving this problem by obtaining the keys with LU-decomposition of a symmetric matrix. Mathematical analysis and computer simulation reveal that the proposed scheme significantly reduces the overhead required for secure connectivity and energy efficiency of the sensor nodes compared to the existing approaches. The superiority of the proposed scheme becomes more substantial when the memory size of the sensor nodes is small.